2020
DOI: 10.1186/s12966-020-01036-0
|View full text |Cite
|
Sign up to set email alerts
|

The physical activity parenting practices (PAPP) item Bank: a psychometrically validated tool for improving the measurement of physical activity parenting practices of parents of 5–12-year-old children

Abstract: Background Many tools have been developed to measure physical activity parenting practices (PAPP). Currently, there is little standardization on how PAPP constructs are operationalized for 5–12 year-old children. Given this lack of consistency our team have started the process of standardizing the measurement of PAPP by developing an item bank which was conceptually informed by 24 experts from 6 countries. Purpose The purpose of this paper is to present the psychometric properties of the PAPP item bank using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…The purpose of this study was to examine the associations between the physical activity parenting practices (PAPP) Structure, Autonomy promotion, and Neglect/control, and children’s physical activity measured with accelerometry while considering a moderating effect of the children’s activity style. To our knowledge, this is the first study exploring the effect of a child’s physical activity style as moderator between PAPP and a child’s physical activity, using items from the updated item bank developed by Masse et al [ 33 ]. Although no significant associations were found in our analyses, our conceptual model showed acceptable fit to the data, suggesting that activity style should be further explored as a moderator when analyzing the relationship between PAPP and children’s physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The purpose of this study was to examine the associations between the physical activity parenting practices (PAPP) Structure, Autonomy promotion, and Neglect/control, and children’s physical activity measured with accelerometry while considering a moderating effect of the children’s activity style. To our knowledge, this is the first study exploring the effect of a child’s physical activity style as moderator between PAPP and a child’s physical activity, using items from the updated item bank developed by Masse et al [ 33 ]. Although no significant associations were found in our analyses, our conceptual model showed acceptable fit to the data, suggesting that activity style should be further explored as a moderator when analyzing the relationship between PAPP and children’s physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tested a new conceptual model using SEM between PAPP and children’s physical activity and sedentary behavior assessed by accelerometry, with the inclusion of children’s activity style as a moderating factor. It was a strength of the study that we used the PAPP domains that have recently been updated and have shown good psychometric properties [ 33 ]. A limitation to the items used to assess the children’s activity style [ 24 ] was that only three out of five items were used in this study, although this decision was made to keep the response burden low.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations